'The Great Bowyer Bible': Robert Bowyer and the Macklin Bible1. Issue 1 (1st August 2021) - Billingsley, Naomi
This article examines an iconic example of grangerizing: the Macklin Bible extra-illustrated in 45 volumes by London artist and bookseller Robert Bowyer (1758‐1834) in the first quarter of the nineteenth century (Bolton Libraries and Museums, Bolton, United Kingdom). The principal focus is on the Bowyer Bible as an example of an extra-illustrator's close engagement with its source publication. The author argues that Bowyer's practice responds not only to the Bible or the King James Bible, in general, but also to the Macklin Bible, in particular. The article discusses how the Bowyer Bible engages with the Macklin Bible specifically and how it reflects a broader range of concerns in its visual engagement with the Bible. It demonstrates that Bowyer's curation of biblical visual material evidences both his professional interests as a connoisseur of prints and his personal interests in the visual culture of the Bible that reflect his own piety as well as contemporaneous developments in the study of the scriptures. Other matters discussed in the article are the original function of this Bible, as well as the extent to which it reflects and is distinctive from contemporaneous extra-illustrated books.